Stereotypical Frames if the Image of Women in the Iraqi TV Drama after 2003 - Al-Jubouri, Irada Zeidan; Hashim, Abraj (ALBAHITH ALALAMI, 2017)
This study aims to deliver the woman’s image and to unveil on how to be introduced in the TV series. The research is based on the survey method-using content analysis tool. The research sample represented in the TV series produced by the IMN, which were displayed in 2014 and used the pattern of Margaret Gallagher to analyze the content of the series in accordance with the frame analysis theory. The study came up with declination of the woman’s representation compared with man in Iraqi TV drama, also the study finds that the series introduced the woman according to the personal, social, political, and economic frames in a standardizing method. It focuses on the characteristics always attributed to it as showing her obedient of the social role and restrained with the customs and traditions and relies on the man and her goals are related with the man except few roles, which bracken such routine.